Laser powder bed fusion (LPBF) of commercially pure titanium and alloy development for the LPBF process - Haase, Fabian; Siemers, Carsten; Rösler, Joachim (Frontiers in Bioengineering and Biotechnology, 2023)
Laser powder bed fusion (LPBF) of titanium or titanium alloys allows fabrication of geometrically more complex and, possibly, individualized implants or osteosynthesis products and, thus, could improve the outcome of medical treatments considerably. However, insufficient LPBF process parameters can result in substantial porosity, decreasing mechanical properties and requiring a post-treatment. Furthermore, texturized parts with anisotropic properties are usually obtained after LPBF-processing, limiting their usage regarding medical applications. The present study addresses both. First, a design of experiments is used in order to establish a set of optimized process parameters as well as a process window for LPBF-printing of small CP-Titanium parts with minimized volume porosity. Afterwards, first results regarding the development of a biocompatible titanium alloy designed for LPBF-processing of medical implants with improved solidification and more isotropic properties are presented on the basis of conventionally melted alloys. This development was performed on the basis of Ti-0.44O-0.5Fe-0.08C-0.4Si-0.1Au, a near-\textalpha-alloy presented by the authors for medical applications and conventional manufacturing, with yttrium as well as boron additions as additional growth restriction solutes. In terms of LPBF-processing of CP-Titanium Grade~1 powder, a high relative density of approx. 99.9% was obtained in the as-printed state regarding the volume of a small cubical sample by using the optimized laser power, scanning speed and hatch distance in combination with a rotating scanning pattern. Moreover, tensile specimens processed with these volume settings and tested in the as-printed, milled state exhibit an high average yield and ultimate tensile strength of approx. 663 and 747~N/mm2, respectively, combined with a high average ductility of approx. 24%. X-ray diffraction results suggest anisotropic mechanical properties, which are, however, less pronounced in terms of the tested specimens. Regarding alloy development, results show that yttrium additions lead to a considerable microstructure refinement, but have to be limited due to the occurrence of a large amount of precipitations and a supposed higher propensity for the formation of long columnar prior \textbeta-grains. However, phase/texture as well as microstructure analysis indicate that Ti-0.44O-0.5Fe-0.08C-0.4Si-0.1Au-0.1B-0.1Y is a promising candidate to achieve lower anisotropy during LPBF-processing, but further investigations regarding LPBF-printing as well as Y2O3 formation are necessary.